KANDUNGAN LIGNIN DAN SELULOSA PADA TUMPI JAGUNG YANG DIFERMENTASI MENGGUNAKAN DUA JENIS PROBIOTIK YANG BERBEDA: LIGNIN AND CELLULOSE CONTENT IN CORN TUMPI FERMENTED USING TWO DIFFERENT PROBIOTIC TYPES - Ferdiansyah, David Rifai; Sukaryani, Sri (Tropical Animal Science, 2025)
Corn tumpi is a waste from threshing corn, has the potential as an alternative feed material but the high lignin and cellulose content inhibits digestion. The research aims to determine the effect of corn tumpi fermentation using two different types of probiotics EM4 and MA11 on lignin and cellulose content. The experimental desaign used was a Completely Randomized Design (CRD) with a one-way pattern with 3 types of treatments and 8 replications, with fermentation for 7 days. The treatments applied were T0: 250 grams of corn tumpi + 2 grams of urea + 5 cc molasses; T1: 250 grams of corn tumpi + 2% MA11 + 2 grams of urea + 5 cc molasses; and T2: 250 grams of corn tumpi + 2% EM4 + 2 grams of urea + 5 cc molasses. The results showed that the average cellulose content in P0 was 23.54%; P1 was 15.95% and P2 was 14.18%, while the average lignin content achieved by the P0 treatment was 23.54%; P1 was 18.09% and P2 was 18.63%. This research can be concluded that the use of probiotics MA-11 and EM4 in corn tumpi fermentation can reduce cellulose and lignin content very significantly (P < 0,01).